Characterizing the multidimensionality of microplastics across environmental compartments. (1st September 2021) - Kooi, Merel; Primpke, Sebastian; Mintenig, Svenja M.; Lorenz, Claudia; Gerdts, Gunnar; Koelmans, Albert A.
Highlights: Meta-analysis of properties of >60, 000 environmental microplastic particles. Particle length, width, area, volume and mass distributions were parameterized. Particle size distributions vary for different compartments and polymer types. The parametrized distributions provide the metrics for dose and effects. As such, this captures the multidimensionality of microplastic in risk assessment. Abstract: Understanding the multidimensionality of microplastics is essential for a realistic assessment of the risks these particles pose to the environment and human health. Here, we capture size, shape, area, polymer, volume and mass characteristics of >60, 000 individual microplastic particles as continuous distributions. Particles originate from samples taken from different aquatic compartments, including surface water and sediments from the marine and freshwater environment, waste water effluents, and freshwater organisms. Data were obtained using state-of-the-art FTIR-imaging, using the same automated imaging post-processing software. We introduce a workflow with two quality criteria that assure minimum data quality loss due to volumetric and filter area subsampling. We find that probability density functions (PDFs) for particle length follow power law distributions, with median slopes ranging from 2.2 for marine surface water to 3.1 for biota samples, and that these slopes were compartment-specific. Polymer-specific PDFs for particle length demonstrated significant differences in slopes among polymers, hinting at polymer specific sources, removal or fragmentation processes. Furthermore, we provide PDFs for particle width, width to length ratio, area, specific surface area, volume and mass distributions and propose how these can represent the full diversity of toxicologically relevant dose metrics required for the assessment of microplastic risks. Graphical abstract: Image, graphical abstract